Fungi as Environmental Guardians: Enzymatic Solutions to Pollution - Vikas Pandey; Mohinee Kumari (International Journal of Fungi, 2025)
Fungi are simple and inexpensive to cultivate, like miniature factories. Their enzymes are more environmentally friendly and safer for all to use compared to the use of dangerous chemicals. This review delves into how scientists are employing these enzymes to clean up polluted soil, purify wastewater, and even convert waste into valuable products such as biofuels.For example, fungi are amazing at cleaning! They create enzymes, which act as little workers and break down a variety of unpleasant environmental materials. This document? It all comes down to those workhorses of fungal enzymes. We examine a variety of types, such as starch amylases, wood ligninases, and plant cellulases. These enzymes have the ability to decontaminate, like pesticides from land and dyes from water. The paper critically evaluates the potential of fungal enzymes in wastewater treatment, organic waste conversion into bio-based products, and environmental remediation. However, there are substantial differences in the efficacy of these enzymes, therefore optimizing them is a step toward enhancing their catalytic capacities. Enhancing fungal strains to produce more enzymes through genetic engineering or environmental parameter optimization could result in improved enzyme kinetics. Last but not least, more research is required to scale up and lower the cost of employing fungal enzymes so that they can be widely used to produce ecologically friendly remedies for environmental contamination. One of the main opportunities for advancing green technology for environmental remediation is to unleash the full potential of fungal enzymes.
Keywords: Environmental Guardians; Enzymatic; bioremediation; fungal enzymes; fungi